2015
DOI: 10.1063/1.4906282
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz magneto-optical spectroscopy of a two-dimensional hole gas

Abstract: We have used terahertz (THz) magneto-optical spectroscopy to investigate the cyclotron resonance in high mobility two-dimensional electron and hole systems. Our experiments reveal long-lived (~20 ps) coherent oscillations in the measured signal in the presence of a perpendicular magnetic field. The cyclotron frequency extracted from the oscillations varies linearly with magnetic field for a two-dimensional electron gas (2DEG), as expected. However, we find that the complex non-parabolic valence band structure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Furthermore, Γ SR is inversely proportional to the carrier effective mass, m * , indicating that SR decay of CR is stronger in narrow bandgap semiconductors, e.g., InSb. In a 2D hole gas (2DHG), on the other hand, weaker SR decay is expected due to the much heavier effective mass; this was confirmed by recent experiments in a highmobility GaAs 2DHG, where Γ SR was comparable with the intrinsic dephasing rate γ ⊥ [167]. In general, SR decay of CR could also happen in 3D semiconductors, but the scattering rate there is expected to be higher because of a continuous spectrum of carriers.…”
Section: Theory Of Superradiant Decay Of Coherent Crmentioning
confidence: 73%
“…Furthermore, Γ SR is inversely proportional to the carrier effective mass, m * , indicating that SR decay of CR is stronger in narrow bandgap semiconductors, e.g., InSb. In a 2D hole gas (2DHG), on the other hand, weaker SR decay is expected due to the much heavier effective mass; this was confirmed by recent experiments in a highmobility GaAs 2DHG, where Γ SR was comparable with the intrinsic dephasing rate γ ⊥ [167]. In general, SR decay of CR could also happen in 3D semiconductors, but the scattering rate there is expected to be higher because of a continuous spectrum of carriers.…”
Section: Theory Of Superradiant Decay Of Coherent Crmentioning
confidence: 73%
“…The higher mobility than our previous report of m~6 10 5 cm 2 V −1 s −1 (t~30 tr ps) for 0.8% strain may be linked to the larger E HH,LH . The apparent oscillation in t THz at different filling factors may be related to the variation in LL occupancy [32][33][34], as the CR linewidth depends on the width of the unoccupied region of the final LL. This point is elucidated in the JDOS description later in the manuscript.…”
Section: Mobilitymentioning
confidence: 99%
“…THz TDS combined with magnetic field at low temperature provides a well-established method to further investigate and understand the dynamical properties of carriers in 2D electronic systems. Recently, it has been found that the cyclotron resonance frequency exhibits a nonlinear dependence on the applied magnetic field using THz MO spectroscopy in a 2D hole gas [12]. Most recently, it was reported that the LLs of electrons and MO transport properties in a 2D material can be significantly modulated by placing it onto a substrate, and the electron-impurity scatterings should not be neglected [13][14][15].…”
Section: Introductionmentioning
confidence: 99%